2009 25th Annual IEEE Semiconductor Thermal Measurement and Management Symposium 2009
DOI: 10.1109/stherm.2009.4810774
|View full text |Cite
|
Sign up to set email alerts
|

Study of an LED device with vibrating piezoelectric fins

Abstract: This study examines an innovative design of a proposed vibrating fin for thermal management of an LED device. The vibrating fin, coated with thin copper and composed of piezoelectric material, can vibrate and conduct heat from the finned base using the piezoelectric effect. This innovative heat-dissipation device can easily break the thermal boundary layer to enhance heat-transfer rate by changing the convective heat-transfer coefficient. In this study, three-dimensional transitional models for the vibrating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The study revealed that vibration enhances heat transfer and achieves a maximum temperature reduction of 35% at the fin tip. In their numerical investigation, Ma et al [43] examined the thermal performance of six piezo-actuated fins and observed an 11.6% enhancement in thermal effectiveness. Another numerical study by Dey and Chakraborty [44] focused on the impact of piezoactuated fin motion with a static substrate on heat-transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that vibration enhances heat transfer and achieves a maximum temperature reduction of 35% at the fin tip. In their numerical investigation, Ma et al [43] examined the thermal performance of six piezo-actuated fins and observed an 11.6% enhancement in thermal effectiveness. Another numerical study by Dey and Chakraborty [44] focused on the impact of piezoactuated fin motion with a static substrate on heat-transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…The application of multiple magnetic-piezoelectric fans on LEDs lighting and electronics was also investigated to assess its thermal performance. Theoretical and simulation models were developed in previous studies [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [15] examined an innovative design of a vibrating fins cooling system. A three-dimensional simulated model for the cooling system was built to investigate its performance.…”
Section: Introductionmentioning
confidence: 99%